REORIENTASI HUKUM KELUARGA DI INDONESIA: (Studi Perlindungan Hak Anak) - Zuhrah, Fatimah; Ardiansyah, Ardiansyah (TAQNIN: Jurnal Syariah dan Hukum, 2019)
The number of cases of violence against children that occur is considered as one indicator of the poor quality of child protection in Indonesia. The existence of children who have not been able to live independently certainly needs people as a place of refuge. The efforts to protect children's rights are a very important and urgent matter to discuss. Important and urgent considering that in recent years we have often been treated to various news and information about various acts of violence against children carried out by people who should be responsible for protecting these children. Islamic discourse and family law literature on the protection of children's rights is still very little to be found. Islamic Compilation of Law (KHI) and Indonesian Marriage Law No. 1 of 1974 does not explicitly discuss the protection of the rights of children to legal sanctions for violators of children's rights in their articles. Likewise with some classical Jurisprudence literature does not concretely discuss the protection of children's rights and legal sanctions for violators of children's rights. This certainly has an impact on understanding and practices that occur in the community towards the pattern of protection of children's rights. This study will look at the concept and the development of child rights protection in Islamic family law and it’s concrete effort of Islamic family law in the protection of children's rights. This qualitative research method is a socio-legal study with a case approach. The findings of this study are in fact, many children are neglected in their lives, both in families who are still intact, father and mother, especially in families whose parents are separated (divorced). Child protection in Indonesia has not been comprehensively accommodated, this is because many children still do not get their rights. The factors include the lack of the role of parents regarding their obligations related to the rights of their children.